Adaptation of a bacterial membrane permeabilization assay for quantitative evaluation of benzalkonium chloride as a membrane-disrupting agent12. Issue 7 (18th May 2017) - Gravel, Julien; Paradis-Bleau, Catherine; Schmitzer, Andreea R.
Abstract : We describe the use of the ortho -nitrophenyl-β-galactoside (ONPG) assay developed by Lehrer et al. to which a new mathematical data treatment was applied. Abstract : We describe the use of the ortho -nitrophenyl-β-galactoside (ONPG) assay developed by Lehrer et al. to which a new mathematical data treatment was applied. In this simplified assay, only one enzymatic assay is needed to provide direct evidence of the kinetics of Escherichia coli membrane permeabilization induced by different concentrations of benzalkonium chloride (BAC ). Analysis of the data obtained from the revised ONPG assay with our adapted mathematical formula indicates thatBAC induces permeabilization of the bacterial outer and inner membranes in a two-step process. The two effective concentration (EC50 ) values obtained in this study, combined with the results from an outer membrane permeabilization assay, suggest that the two steps observed in the permeabilization process are related to the two different bacterial membranes. We show that membrane permeabilization occurs very fast upon the addition of bacterial cells to theBAC solutions and demonstrate that sub-lethal concentrations ofBAC disturb the integrity of the Gram-negative bacterial membranes. Overall, our work broadens our knowledge on the mode of action ofBAC on bacterial cells and emphasizes thatBAC, and quaternary ammonium compounds in general, should not be used at sub-lethal concentrations in order to lower the risk of bacterial tolerance and resistance to antibiotics.